O universo visual dos xamãs wauja (Alto Xingu) - Aristóteles Barcelos Neto (Journal de la Société des Américanistes)
The visual universe of Wauja shamans (Upper Xingu). This paper analyses the shaman’s visual experiences in dreams and trances as elements in the conceptualisation of the four main types of non-human beings (« animal-people », « clothing », « monster », and « animal ») and of their relationships to the Wauja. The pictures included in the article derive from the ontological and esthetic reflexions of a privileged group of individuals. These individuals are recognized as possessing specific powers for interpreting facts and visual or verbal expressions of Wauja cosmological ideas.